2021
DOI: 10.1109/tetc.2018.2865345
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Signature Verification in the Mobile Cloud Scenario: Survey and Way Ahead

Abstract: On-line signature verification is typically carried out with the use of digitizing tablets specifically designed for the aim. So far, stand-alone systems have been mainly inspected, but the current distributed/cloud scenario and the amount of mobile devices in everyday life is calling for a new challenge. Within this scenario, signatures are acquired around the world with different kinds of devices and processed on multiple platforms in order to be verified. Through the paper, the different phases of the signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 99 publications
(179 reference statements)
0
18
0
Order By: Relevance
“…Function-based online signature verification relies nowadays on the acquisition of handwriting specimens using various sensors that provides position, length, velocity, acceleration, pressure, force, direction of movement, pen inclination as a function of time [1][2][3]. Most of these studies are run using the same set up (or a few of these) involving an instrumented stylus coupled to a passive or active writing display.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Function-based online signature verification relies nowadays on the acquisition of handwriting specimens using various sensors that provides position, length, velocity, acceleration, pressure, force, direction of movement, pen inclination as a function of time [1][2][3]. Most of these studies are run using the same set up (or a few of these) involving an instrumented stylus coupled to a passive or active writing display.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been demonstrated that there are three classes of individuals regarding pressure control, stable, unstable and piecewise time stable [7], many automatic signature verification systems use pressure information in a signal-based or feature-based approach [2]. But is the pressure signal reliable, from one device to another?…”
Section: Introductionmentioning
confidence: 99%
“…The relative improvement for all user categories is of at least 93% compared to the usual signature.Sensors 2020, 20, 933 2 of 21 sensor technology, interoperability, setting several new challenging issues that impact verification performance [2,17].Usually, for improving verification performance, different strategies were exploited in the literature: (i) acquiring signatures in controlled conditions [1-16]; (ii) using a high quality sensor (such as a Wacom tablet) with high temporal and spatial resolution, and able to capture other time functions than pen coordinates, as pen pressure and pen inclination angles [18]; (iii) selecting reference signatures in order to control intra-personal variability [19][20][21]; (iv) extracting several features for signature description (as pressure, speed, and acceleration, etc.) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] or by means of a deep neural network [2,[22][23][24][25].However, some of these strategies are no longer possible in the mobile scenario: as pointed out by [17], the sensors are not of the same quality, in terms of temporal resolution in particular, acquisition conditions are highly variable, and some sensors are limited to the capture of only pen coordinates. In the so-called "cloud scenario" [17], users acquire their signatures as they want, standing, sitting or moving, handling the device on the hand at different angles or orientations, or placing it on any support.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] or by means of a deep neural network [2,[22][23][24][25].However, some of these strategies are no longer possible in the mobile scenario: as pointed out by [17], the sensors are not of the same quality, in terms of temporal resolution in particular, acquisition conditions are highly variable, and some sensors are limited to the capture of only pen coordinates. In the so-called "cloud scenario" [17], users acquire their signatures as they want, standing, sitting or moving, handling the device on the hand at different angles or orientations, or placing it on any support. A smartphone is usually handheld, while a tablet may be placed on the desktop or sustained by the left arm if the writer is right-handed.…”
mentioning
confidence: 99%
See 1 more Smart Citation